Un bâtiment comme appareil de vision d’une multiplicité d’images-fragments du paysage et de l’histoire de Berlin - Laurence Kimmel (Appareil)
In the Dutch Embassy in Berlin, constructed by OMA/Rem Koolhaas in 2003, open corridors indicate several buildings of the city (TV tower, Altes Stadthaus, a National Socialist building) and several elements of the natural landscape, such as the Spree River, in a montage of architectural framings. Through this montage, the visitor sees fragments of the city that are more or less recognizable. Fragments are not romantic ones; they are more like Walter Benjamin’s fragments of the city of Berlin that sought to be in a constellation of singularities in order to produce some sort of sense. Koolhaas’s architectural promenade is trying to produce that sense through continuity in the experience of the visitor. Like Aby Warburg’s images in the process of writing art history, the successful use of these images can give the viewer a sense of the history of Berlin.